CT features with histopathological correlation in inflammatory versus benign & malignant neoplastic appendiceal mucoceles: a retrospective cross-sectional study - Kumail Khandwala; Nida Sajjad; Dawar Burhan Khan; Amyn A. Malik; Wasim Ahmed Memon; Muhammad Owais Rao; Nasir Ud Din; Faheemullah Khan; Khabab Abbasher Hussien Mohamed Ahmed (BMC Gastroenterology)
Abstract Background & objectives Differentiation of histologic subtypes of appendiceal mucoceles may prove to be difficult on computed tomography (CT). The main objective of this study was to identify the CT features of mucocele of the appendix and correlate the imaging findings with histopathology in inflammatory, benign, and malignant neoplastic lesions, and whether these entities can be accurately differentiated on CT imaging. Materials and methods CT scans of 31 patients with diagnosis of appendiceal mucocele were retrospectively reviewed and compared with histopathology. The appendix was evaluated for maximal luminal diameter, cystic dilatation, luminal attenuation, appendicolith, mural calcification and enhancement, periappendiceal fat stranding and fluid. CT findings were compared by use of Mann-Whitney U and Fisher’s exact tests. Receiver operating characteristics analysis was performed to assess the diagnostic utility of appendiceal luminal diameter in differentiating different types of mucoceles. Results Patients were classified into three groups: those with inflammatory mucoceles (n = 10), benign mucoceles (simple mucocele, mucosal hyperplasia and low-grade appendiceal mucinous neoplasm (n = 17), and those with malignant mucinous adenocarcinoma (n = 4). The mean diameter was found to be significantly different in the three groups with the largest diameter in the benign subgroup. Soft tissue thickening (p-value 0.01), mural calcification (p-value < 0.01), internal septation (p-value 0.02) and fat stranding (p-value 0.05) was found to be of statistical significance among the various groups. The best cut-off diameter for diagnosis of inflammatory mucoceles to be ≤ 2.3 cm with a sensitivity of 71% and specificity of 90%. Conclusion Our study suggests that CT findings such as appendiceal diameter less than 2.3 cm, absence of soft tissue thickening, mural calcification and internal septation may be useful in preoperative diagnosis of inflammatory appendiceal mucocele.